PENERAPAN DATA MINING DALAM MENENTUKAN PRIORITAS TINDAKAN MEDIS PASIEN BPJS BERDASARKAN RIWAYAT MEDIS MENGGUNAKAN METODE KNN - Wilson Panjaitan; Dicky Apdillah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The rapid development of information technology has encouraged the healthcare sector to utilize data as a basis for faster, more precise, and effective decision-making. One of the largest data sources in the healthcare sector is BPJS (Social Security Administration for Health) patient data, which includes medical history, examination results, previous medical procedures, and medication use. This data is a critical asset that, when properly managed and analyzed, can assist hospitals and healthcare facilities in determining appropriate medical interventions for patients. The purpose of this study was to design and develop an application for prioritizing medical procedures for BPJS patients in, using the KNN method, the PHP programming language, and a MySQL database. The data used in this study were BPJS patient visit data. Based on test results at various levels of K=3, K=5, and K=7, the data demonstrated very high consistency. Even though the K value (number of nearest neighbors) was increased from 3 to 7, the final classification results still showed a predominance of the Medium Priority category. With a KNN-based classification system, medical personnel no longer need to manually assess each patient.